Diseño de un modelo de indicadores de Gestión para evaluar el desempeño del personal del Centro de Salud Pública, tipo A Guasaganda, Provincia de Cotopaxi, Ecuador, año 2022 - Esquivel García, Alba Wendalina (2023)
In the year 2022, at the Public Health Center, Type A Guasaganda, located in the province of Cotopaxi, Cantón La Mana, an investigation was carried out whose objective was to determine a model of management indicators aimed at evaluating the performance of the personnel . This study was carried out under a descriptive mixed approach and was carried out through semi-structured interviews based on the Technical Regulations of the Performance Evaluation Subsystem. The data analysis was done using the tool called 9 box, which resulted in the majority of the personnel being in performance group B, which is characterized by: high potential, low performance; half potential, half performance; and low potential, high performance.